Implementasi ESG sebagai Instrumen Keberlanjutan Koperasi Konsumen dalam Perspektif Ekonomi Syariah - Indah Nofita Sari; Romzatul Widad; Moh. Idil Ghufron (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
This study examines the implementation of Environmental, Social, and Governance (ESG) principles as a sustainability instrument for consumer cooperatives from the perspective of Islamic economics. Consumer cooperatives, as people-based economic institutions, face significant challenges in maintaining sustainability amid rapid economic transformation and increasing demands for corporate accountability. ESG, as a global framework for measuring sustainability performance, is considered relevant to the values of Islamic economics which emphasize justice, transparency, social benefit, and environmental responsibility. This research uses a qualitative approach through literature study and document analysis to formulate a conceptual model of ESG implementation in consumer cooperatives based on Islamic economic principles. The findings show that ESG dimensions are in line with maqashid al-syariah, namely the protection of religion, life, intellect, lineage, and property. Environmental aspects correlate with the stewardship principle of khalifah fil ardh, while social aspects align with the concept of takaful ijtima’i, and governance reflects the values of amanah and shura. This study offers a conceptual framework for integrating ESG within the cooperative institutional governance system as a strategic step toward sustainable and equitable economic development.